First-order transition in trigonal structure CaMn2P2. (28th December 2020) - Li, Y. J.; Jin, F.; Mi, Z. Y.; Guo, J.; Wu, W.; Yu, Z. H.; Wu, D. S.; Na, S. H.; Mu, C.; Zhou, X. B.; Li, Z.; Liu, K.; et al.
Abstract: We report structural and physical properties of the single crystalline . The X-ray diffraction (XRD) results show that adopts the trigonal -type structure. Temperature-dependent electrical resistivity measurements indicate an insulating ground state for with activation energies of 40 meV and 0.64 meV for two distinct regions, respectively. Magnetization measurements show no apparent magnetic phase transition under 400 K. Different from other, Sr, and Ba, and, As, and Sb) compounds with the same structure, heat capacity and reveal that has a first-order transition at and the transition temperature shifts to high temperature upon increasing pressure. The emergence of plenty of new Raman modes below the transition, clearly suggests a change in symmetry accompanying the transition. The combination of the structural, transport, thermal and magnetic measurements points to an unusual origin of the transition.